Globalization, Transparency and Economic Growth: The Vulnerability of Chinese Firms to Macroeconomic Shocks - Lars Oxelheim (Research Institute of Industrial Economics (IFN), 2008)
The process of globalization encompasses economic and financial integration. Abolition of capital controls and dismantling of barriers of different kinds are important ingredients of the process that will entirely change the exposure of previously sheltered companies to shocks on the global economic arena. Lessons learned by policy-makers in already globalized countries are that market participants should be prepared to meet the new exposure to fluctuating exchange rates, interest rates and inflation rates. China has recently adopted International Financial Reporting Standards (IFRS) in her efforts to improve the quality of information available for risk management and for pricing of risk. This paper claims that further improvements are needed and presents a new framework for how to understand and measure the impact of different scenarios on corporate performance. It also elaborates on how to communicate the macroeconomic effects to external stakeholders of the firm in a way that fosters further economic growth in China.
Keywords: E22; E32; E44; F15; F23; F37; G18; G32; L25; M21; 330; International Financial Reporting Standards; Transparency; Economic Growth; Macroeconomic Impact; Globalization; IFRS; Unternehmenserfolg; Wirtschaftswachstum; Globalisierung; Konjunktur; Schock; Makroökonomischer Einfluss; China